Правова природа інвестиційних відносин: фінансово-правове регулювання - Бліхар, Марія Миронівна (Національний університет "Львівська політехніка", 2018)
Дисертацію присвячено формуванню концепції фінансово-правової регламентації суспільних відносин у сфері інвестиційної діяльності, яка може бути використана з метою розроблення комплексних підходів до реформування вітчизняного фінансово-інвестиційного правового регулювання. Розкрито фінансово-правову природу відносин, пов’язаних з інвестиційною діяльністю, проаналізовано публічність як підставу виокремлення фінансово-інвестиційних правовідносин. Класифіковано суб’єктів інвестування, охарактеризовано їх фінансово-правову компетенцію. Досліджено об’єкт інвестування з позиції науки фінансового права, встановлено його склад, здійснено диференціацію. Визначено об’єкт інвестиційної діяльності в бюджетній сфері, виділено його види і форми. Сформульовано дефініцію бюджетного інвестування, розкрито його риси. З’ясовано специфіку суб’єктного складу бюджетно-інвестиційних правовідносин. Досліджено стадійність як природну властивість бюджетно-інвестиційного процесу, встановлено особливості правової регламентації інвестування на його окремих стадіях. Виділено специфіку податково-інвестиційних правовідносин, розглянуто їхню структуру. Здійснено класифікацію та характеристику податкових платежів, дотичних до інвестування. Сформульовано дефініцію інвестиційного податкового платежу, виокремлено групу відповідних платежів. Окреслено специфіку податково-процедурного регулювання у сфері інвестиційної діяльності. Запропоновано класифікацію податкових режимів, що застосовуються під час здійснення інвестування (загальний, спеціальний, особливий). Сформульовано визначення фінансового контролю в інвестиційній сфері та охарактеризовано компетенцію відповідних органів, що здійснюють фінансовий контроль. Вироблено структурування зазначеного контролю за такими критеріями, як вид, форма, метод. Проаналізовано фінансово-правовий аспект контрольно-інвестиційних процедур. Досліджено фінансову складову системи юридичної відповідальності у сфері інвестиційної діяльності (її підстави, функції та різновиди). Аргументовано важливість створення низки спеціалізованих органів / установ у сфері інвестування. Сформульовано пропозиції та рекомендації щодо внесення змін до чинного вітчизняного законодавства, спрямованих на вдосконалення фінансово-правового регулювання інвестицій. Диссертация посвящена формированию концепции финансово-правовой регламентации общественных отношений в сфере инвестиционной деятельности. Концепция может быть использована в процессе разработки комплексных подходов к реформированию отечественного финансово-инвестиционного правового регулирования. В работе раскрывается финансово-правовая природа отношений, касающихся инвестиционной деятельности. Анализируется публичность как основание для вычленения финансово-инвестиционных правоотношений. Предложена классификация субъектов инвестирования, охарактеризована их финансово-правовая компетенция. Исследован объект инвестирования с позиции науки финансового права, установлен его состав, осуществлена дифференциация. Определен объект инвестиционной деятельности в бюджетной сфере, выделены его виды и формы. Сформулирована дефиниция бюджетного инвестирования, раскрыты его признаки. Описана специфика субъектного состава бюджетно-инвестиционных правоотношений. Исследована стадийность как естественное свойство бюджетно-инвестиционного процесса, определены особенности правовой регламентации инвестирования на его отдельных стадиях. Установлена специфика налогово-инвестиционных правоотношений, рассмотрена их структура. Даны классификация и характеристика налоговых платежей, связанных с инвестированием. Предложена дефиниция инвестиционного налогового платежа, вычленена группа соответсвующих платежей. Очерчена специфика налогово-процедурного регулирования в сфере инвестиционной деятельности. Предложена классификация налоговых режимов, применяемых при осуществлении инвестирования (общий, специальный, особенный). Сформулировано определение финансового контроля в инвестиционной сфере, характеризуется компетенция соответствующих органов, осуществляющих финансовый контроль. Указанный контроль структурируется по следующим критериям: вид, форма, метод. Анализируется финансово-правовой аспект контрольно-инвестиционных процедур. Исследуется финансовая составляющая системы юридической ответственности в сфере инвестиционной деятельности (ее основания, функции и разновидности). Аргументируется необходимость создания ряда специализированных органов / учреждений в сфере инвестирования. Формулируется ряд предложений и рекомендаций, касающихся усовершенствования финансово-правового регулирования инвестирования в действующем отечественном законодательстве. The thesis is devoted to the formation of the concept of financial and legal regulation of public relations in the sphere of investment activity, which can be used to develop integrated approaches to reforming the domestic financial and investment legal regulation. The main directions of financial and legal regulation in the sphere of investment activity (budget vector, tax direction, control-delictual vector, currency vector) are outlined. The financial and legal nature of relations connected with investment activity is disclosed and the publicity as the basis for distinguishing financial and investment legal relations is analyzed. The investment subjects are classified and the characterization of their financial and legal competence is carried out. The criteria (quantitative parameter, qualitative indicator) of assigning a person to an investor are determined. The object of investment from the position of the science of financial law is investigated, its composition is established and its differentiation is carried out. The author’s definitions of the concepts of “financial and investment legal policy” and “financial and investment security” are formulated. The necessity of formation and adoption of the Strategy of financial and investment security of Ukraine by the Verkhovna Rada of Ukraine is established. The distinguishing of financial and investment law as a component of the science of financial law and the autonomous academic discipline is proposed, and the program of the corresponding special course is developed. The impropriety of the adoption of the Investment Code of Ukraine as an act that, by its nature and purpose, is aimed at dissolving the sustained sectoral and institutional ties, is proved. The object of the investment activity in the budget sphere is defined, and its types and forms are distinguished and classified. The distinction between the subject and the object of investment in the budget sphere is made. The definition of the budget investment is formulated and its features are revealed. The specificity of the subject composition of the budget-investment legal relations is clarified, and their differentiation onto conditionally passive subjects, active subjects-organizers, direct subjects-donors and direct subjects-recipients is carried out. The stage as a natural feature of the budget-investment process is investigated, the peculiarities of the legal regulation of investment at its separate stages are established. The specificity of the tax-investment legal relations (their special “working area”, the complex nature of investment activity, the special object – investments and investing) is highlighted, and their structure is considered. The tax legal relations in the sphere of investment depending on their type (general regulatory, concrete regulatory, security integrated) are characterized. The classi-fication and characterization of tax payments related to investing are carried out. The definition of the investment tax payment is formulated, the group of appropriate payments (the investment ones by their purpose) is distinguished. The specificity of tax and procedural regulation in the sphere of investment activity is outlined. The classification of tax regimes into general, special (systemic and complex) and specific which are applied in the course of investing, is offered. The common features peculiar for the special tax regimes in the sphere of investment are singled out. The definition of financial control in the investment sphere is formulated and the competence of the appropriate bodies depending on their level and priority directions of activity is characterized. The structuring of the specified control according to such criteria as a kind, form and method is made. The characterization of the types of financial control in the sphere of investment, depending on the direction of control actions in accordance with the identification of the subject and the object of control, information support and the purpose of investment activity, is described. The financial and legal aspect of control-investment procedures is analyzed, the peculiarities of financial and investment control procedures and the basic procedures and stages of financial and investment cont-rol are singled out. The system of legal responsibility in the sphere of investment activity, its structure and specificity as well as financial and legal component (its bases and varieties) are investigated. The description of the functions of legal responsibility for financial and investment violations is carried out. The importance of creating specialized institutions, the institutions in the sphere of investment (Financial and Investment Inspection of Ukraine, the Development Bank, the Investment and Innovation Agency of Ukraine, the Supreme Court on Investment Activity) is proved. A number of suggestions and recommendations for the current domestic legislation aimed at improving the financial and legal regulation of investment are formulated.
Правовая природа инвестиционных отношений: финансово-правовое регулирование
Legal nature of investment relations: financial and legal regulation
Keywords: бюджетно-інвестиційна діяльність; інвестиції; інвестиційні відносини; інвестування; податково-інвестиційні правовідносини; фінансовий контроль; фінансово-правове регулювання; юридична відповідальність; финансово-правовое регулирование; инвестиции; инвестирование; инвестиционные отношения; бюджетно-инвестиционная деятельность; налогово-инвестиционные правоотношения; финансовый контроль; юридическая ответственность; financial regulation; investments; investing; investment relations; budget and investment relations; tax and investment relations; financial control; legal responsibility; 347.73:336.531.2(477)